Different environmental temperatures affect amino acid metabolism in the eurytherm teleost Senegalese sole (Solea senegalensis Kaup, 1858) as indicated by changes in plasma metabolites - Costas, B. (2014)
Senegalese sole (Solea senegalensis) is a eurytherm teleost that under natural conditions can be exposed to annual water temperature ﬂuctuations between 12 and 26C. This study assessed the effects of temperature on sole metabolic status, in particular in what concerns plasma free amino acid changes during thermal acclimation.